An Analysis of University Students’ Social Media Consumption and Vulnerability to Cybercrimes - Joshua Abah; Peter Inalegwu Agada; Taurayi Willard Chinaka; Tatolo Talasi; Imam Rofiki (Research and Innovation in Social Science Education Journal (RISSEJ), 2026)
This study investigates university students’ vulnerability to cybercrimes at a public university in West Africa. The study specifically examines how students’ online behaviours, including password management, data access habits, internet usage, social media practices, and smartphone security, contribute to their susceptibility to cyber threats. The research adopts a survey research design, allowing for the collection of data on students’ cybersecurity behaviours and risk exposure through structured survey questions. A structured online questionnaire was administered to 580 students, and data were analysed using descriptive statistics, including mean, mode and standard deviation. The findings reveal that university students are highly vulnerable to cyberattacks due to low adoption of two-step verification and frequent password reuse, which increase the risk of unauthorized access and credential theft. However, their tendency to avoid sharing passwords, using simple passwords and saving passwords in browsers are positive security habits that reduce some cybersecurity risks. While many students demonstrate responsible cybersecurity habits, significant vulnerabilities remain in data storage and file transfer practices, which could lead to unauthorized access, data breaches, or malware infections. The outcomes indicate that although students show caution in avoiding risky downloads and pirated software, they still engage in high-risk behaviours related to internet and network access in the frequent use of public Wi-Fi, unverified file sharing, pop-up ad interactions, and improper VPN usage, increasing their exposure to cyber threats such as unauthorized access, malware infections, and phishing attacks. Although students demonstrate caution in some aspects of social media use, they remain vulnerable to cybersecurity risks due to excessive personal information sharing, frequent posting, and engagement across multiple platforms, with these behaviours increasing their exposure to privacy breaches, targeted cyber-attacks, and social engineering threats. While students generally avoid high-risk behaviours such as rooting their devices, they remain vulnerable due to inconsistent security practices on their smartphones. University students’ excessive reliance on GPS tracking, automatic synchronization, and lending devices to others increases exposure to privacy breaches, data leaks, and unauthorized access. This study is original in its consideration of the unique demographic characteristics of university students in North Central Nigeria along with their cybercrime vulnerability. The empirical results have established that while some students demonstrate responsible cybersecurity habits, social media usage significantly heightens vulnerabilities to cybercrime. The study underscores the need for targeted cybersecurity awareness programmes and institutional policies to enhance students’ online safety.